Formulation of Nanoemulsion Gel Pogostemon cablin Benth. And Anti-acne Activity - Heroweti, Junvidya; Mindiono, Imam Arif; Mahmud, Nurlela; Pradasari, Frisya; Fresiva, Urva; Prihantini, Malinda (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Patchouli oil (Pogostemon cablin Benth.) contains patchouli alcohol, a compound known for its antibacterial properties, including activity against Propionibacterium acnes (Cutibacterium acnes), a key bacterium implicated in the pathogenesis of acne. This study aims to evaluate the anti-acne potential of a nanoemulsion gel formulation of patchouli oil using three different gelling agents: HPMC (F1), Na CMC (F2), and Carbopol 940 (F3). Each formulation was assessed for its physicochemical characteristics, including color, odor, texture, pH, adhesion, spreadability, viscosity, particle size, polydispersity index (PDI), and zeta potential. All formulations appeared milky white, retained the characteristic aroma of patchouli oil, and exhibited a smooth gel texture. Among the three, F1 demonstrated the highest viscosity, while F3 exhibited superior adhesion. The average pH value (6.19 ± 0.23) was within the acceptable range for topical application. In vivo evaluations indicated that F3 exhibited the most significant reduction in erythema and edema, with minimal irritation potential. Additionally, F3 received the highest respondent satisfaction rating (77.6%), indicating better acceptance. Based on these findings, Carbopol 940 is identified as the most suitable gelling agent for the development of a patchouli oil nanoemulsion gel with promising anti-acne efficacy and favorable respondent acceptability.